2011
DOI: 10.1134/s0006297911110034
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptors as a possible component of store-operated Ca2+ entry in human T-lymphocytes

Abstract: Elevation of intracellular Ca²⁺ in T-lymphocytes as a consequence of T cell antigen receptor activation triggers transcriptional programs resulting in effector cytokine secretion and immune response coordination. Increase of Ca²⁺ concentration in T-lymphocytes follows both the Ins(1,4,5)P(3)-dependent release from an intracellular store and subsequent influx from extracellular milieu. Flow cytometry and the fluorescent dye Fluo-4AM have been used to demonstrate that noncompetitive NMDA receptor antagonist (+)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Gonzalez-Sanchez et al measured SOCE and performed Ca 2+ store depletion in a medium containing physiological Ca 2+ concentrations [53], while we used the more common Ca 2+ re-addition protocol [45,54]. Yet, MK801 did inhibit SOCE in human T-lymphocytes under the conditions of Ca 2+ re-addition protocol [55]. Our results show that the increase in Ca 2+ after its addition can be mainly attributed to SOCE, but an additional small influx of Ca 2+ is also possible due to the activation of synapses.…”
Section: Discussionmentioning
confidence: 93%
“…Gonzalez-Sanchez et al measured SOCE and performed Ca 2+ store depletion in a medium containing physiological Ca 2+ concentrations [53], while we used the more common Ca 2+ re-addition protocol [45,54]. Yet, MK801 did inhibit SOCE in human T-lymphocytes under the conditions of Ca 2+ re-addition protocol [55]. Our results show that the increase in Ca 2+ after its addition can be mainly attributed to SOCE, but an additional small influx of Ca 2+ is also possible due to the activation of synapses.…”
Section: Discussionmentioning
confidence: 93%
“…Although CRAC channels can be activated at low membrane potential, the changed membrane potential will alter open probability and conductivity compared to the normal resting membrane potential. Therefore, the reduced Ca 2ϩ response in the presence of NMDAR antagonists is, at least partially, caused by lowering the Ca 2ϩ influx and by inhibition of the positive feedback function of Ca 2ϩ -induced activation of K Ca 3.1 channels during T-cell activation (56)(57)(58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, NMDA receptors have been shown to be expressed on rodent and human T cells and contribute to the increase in intracellular Ca 2+ level following T cell activation (Lombardi et al, 2001; Boldyrev et al, 2004; Miglio et al, 2005, 2007; Mashkina et al, 2007, 2010). Zainullina et al (2011) further demonstrated that activation of T cells with thapsigargin, an inhibitor of a Ca 2+ -ATPase of the ER that induces Ca 2+ store depletion and activation of plasma membrane Ca 2+ channels, in the presence of an NMDA receptor antagonist did not affect the movement of Ca 2+ from intracellular stores. However, it reduced the influx of Ca 2+ from the extracellular space suggesting that NMDA receptors participate in SOCE, at least to some degree.…”
Section: Important Additional Ca2+ Channels In T Lymphocytesmentioning
confidence: 99%
“…However, it reduced the influx of Ca 2+ from the extracellular space suggesting that NMDA receptors participate in SOCE, at least to some degree. In this scenario, the NMDA receptors may be mainly contributing to Ras/Rac-dependent signaling in T cells following TCR engagement (Zainullina et al, 2011). Analogous to neuronal synapses, a recent study of thymocytes showed that upon TCR stimulation, NMDA receptors localize to the immunological synapse (Affaticati et al, 2011).…”
Section: Important Additional Ca2+ Channels In T Lymphocytesmentioning
confidence: 99%